The Effect of Emotional Intelligence Dimensions on Enhancing Employees’ Eustress at work - Almazrouei, Sultan Ali Suleiman (Information Management and Business Review, 2017)
This paper aims to investigate the effect of dimensions of emotional intelligence which include self-emotions appraisal, other-emotions appraisal, use of emotions, and regulation of emotions on enhancing employees’ eustress at work. A quantitative survey was applied on 483 employees from ministry of education in Oman. PLS based SEM was utilized for analyzing data. The findings showed a significant positive association between others-emotions appraisal, use of emotions, regulation of emotions and employees’ eustress. However, self-emotions appraisal does not influence employees’ eustress significantly. Therefore, managers should foster employees’ emotional intelligence (others-emotions appraisal, use of emotions, regulation of emotions) to enhance employees’ eustress which is essential for work success. Some training sessions pertaining emotional intelligence should be held.